2020
DOI: 10.1123/japa.2019-0297
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Immigrant Muslim Older Adults’ Experiences and Perceptions of Physical Activity

Abstract: Physical activity is essential for healthy aging; however, there has been little exploration of physical activity in Muslim older immigrants in Canada. Over one million Canadians identify as Muslim, the majority is first-generation immigrants, with increasing cohorts entering older age. A community-based participatory research project on healthy aging was conducted with 68 older adults and community members from South Asian, Arab, and African Muslim ethnocultural communities in a Canadian urban center. A combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…For all studies, there was a clear aim, the qualitative methodology was deemed appropriate, they were deemed to have used appropriate research designs with justification, ethical issues had been considered, and there were clear statements regarding the findings. Most studies used appropriate recruitment methods (87%) [29, 30, 32-34, 36-41, 43, 44], and had rigorous methods of data analysis (87%) [29,30,[32][33][34][35][36][37][38][39][40][41]44]. Only seven studies (47%) reported on or provided sufficient detail in order to determine if the relationship between the researcher and participants had been considered [29, 32 ,34, 35, 37, 39, 40].…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…For all studies, there was a clear aim, the qualitative methodology was deemed appropriate, they were deemed to have used appropriate research designs with justification, ethical issues had been considered, and there were clear statements regarding the findings. Most studies used appropriate recruitment methods (87%) [29, 30, 32-34, 36-41, 43, 44], and had rigorous methods of data analysis (87%) [29,30,[32][33][34][35][36][37][38][39][40][41]44]. Only seven studies (47%) reported on or provided sufficient detail in order to determine if the relationship between the researcher and participants had been considered [29, 32 ,34, 35, 37, 39, 40].…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…The studies were published between 1998 [43] and 2020 [29,39]. Five studies were conducted in Australia [29,30,36,41,43], three in the US [33,38,42], three in the Netherlands [34,37,44], three in Sweden [32,35,40], and one in Canada [39]. The target population of the 15 studies included Arab migrant groups from the Middle East and North Africa, with a total of five studies exclusively focusing on Arab migrant samples [29,33,35,38,42].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations